Treating substance abuse is not enough: Comorbidities in consecutively admitted female prisoners. (July 2015) - Mir, Jan; Kastner, Sinja; Priebe, Stefan; Konrad, Norbert; Ströhle, Andreas; Mundt, Adrian P.
Abstract: Introduction: Several studies have pointed to high rates of substance use disorders among female prisoners. The present study aimed to assess comorbidities of substance use disorders with other mental disorders in female prisoners at admission to a penal justice system. Methods: A sample of 150 female prisoners, consecutively admitted to the penal justice system of Berlin, Germany, was interviewed using the Mini-International Neuropsychiatric Interview (MINI). The presence of borderline personality disorder was assessed using the Structured Clinical Interview II for DSM-IV. Prevalence rates and comorbidities were calculated as percentage values and 95% confidence intervals (CIs). Results: Ninety-three prisoners (62%; 95% CI: 54–70) had substance use disorders; n = 49 (33%; 95% CI: 24–42) had alcohol abuse/dependence; n = 76 (51%; 95% CI: 43–59) had illicit drug abuse/dependence; and n = 53 (35%; 95% CI: 28–44) had opiate use disorders. In the group of inmates with substance use disorders, 84 (90%) had at least one other mental disorder; n = 63 (68%) had comorbid affective disorders; n = 45 (49%) had borderline or antisocial personality disorders; and n = 41 (44%) had comorbid anxiety disorders. Conclusions: Female prisoners with addiction have high rates of comorbid mental disorders at admission to the penal justice system, ranging from affective to personality and anxiety disorders. Generic and robust interventions that can address different comorbid mental health problems in a flexible manner may be required to tackle widespread addiction and improve mental health of female prisoners. Highlights: A majority of 62% of females have substance use disorders at admission to prison. Opiates are the most frequent substances of addiction in 35% of this population. Addictions are highly comorbid with affective, personality and anxiety disorders. Comorbidities do not differ between subgroups addicted to different substances. Interventions should be generic, robust and flexible to cover different disorders.